A biblical death-wish: Paul celebrating dying in Phil 1:21 - Punt, J. (Verbum et ecclesia, 2009)
Death features as an important concept in the Pauline writings in the New Testament for a number of reasons. However, the intriguing way in which the apostle at times addressed death as positive notion in itself, was traditionally related to Paul’s theological convictions and his understanding of the death of Christ in particular. The remarkably pointed way in which Paul positively celebrated death in Philippians 1:21 borders on invoking a martyrological paradigm, and raises questions about his convictions regarding life, and bodily existence in particular. Interesting analogies emerge when Paul’s celebration of death is compared in a concluding section with contemporary, popular instances where death is - even if for different reasons - presented as “gain”.